(untitled) (International Journal of Ayurveda and Pharma Research, 2025)
The pathophysiological process of aging is progressive and irreversible, resulting in a loss of tissue and cell activities as well as an increased risk of certain diseases. Diseases like neurodegenerative diseases, cardiovascular diseases, metabolic disorders, musculoskeletal ailments, and immune system disorders are increasingly prevalent among old age. The universal process of aging most likely started with the beginning of life. The accumulation of various harmful aging-related alterations in the cells and tissues gradually reduces function and may ultimately result in death. Aging is one of the many human illness that Ayurveda addresses holistically. It is categorized as a Yapya (palliative) and natural sickness. The body undergoes a number of changes as people age, including changes in mental and cognitive abilities, exterior appearance, Dosha, Dhatu, Mala, Agni, Oja, and other conditions. Ayurveda maintains Dhatu samya (homeostasis) through a comprehensive strategy, for which a number of principles have been outlined. It is believed that aging is an illness that might appear at any time. As a result, a thorough explanation of how to prevent, maintain, and treat aging has been provided; if followed, this will result in a long, healthy life. Method: Survey study, 31 participants from different parts of Kerala who are above 80 years of age was contacted and an online survey via google form was conducted. Objective: To highlight the importance of following Ayurvedic principles for longevity. Result: All the participants were following most of the principles explained in Ayurveda in their daily life. Conclusion – Ayurvedic principles are helping to maintain a healthy long life. So here an effort has been made to document some Ayurvedic principles followed by participants above 80 years of age who lead a healthy long life.